(untitled) (American Journal of Islam and Society, 2011)
Along with Islamic finance and jurisprudence for Muslim minorities, Maqaṣid al-Shariʻah (the higher objectives of Islamic Law) completes the trinity of cutting-edge traditional Islamic research. Its importance emanates from its philosophical vision, which allows for the practice of divine text and prophetic teachings in a manner that acknowledges and responds to contemporary challenges. Recognizing that this vibrant topic is complex, intellectually challenging, and that most books on the subject are written for specialists, the International Institute of Islamic Thought published three introductory guides to provide simple and accessible material for the general reader. The Recognizing that this vibrant topic is complex, intellectually challenging, and that most books on the subject are written for specialists, the International Institute of Islamic Thought published three introductory guides to provide simple and accessible material for the general reader. The series includes the three books above that are the subject of this review. While significantly varying in focus, all three books succeed in providing introductory-level texts. Muhammed Chapra presents one long argument that human well-being and development is realized by enriching the human self, faith, wealth, intellect, and posterity. Before moving on in detail to examine the conditions necessary for the enrichment of faith, wealth, intellect, and posterity, and how the Sharʻiah allows people to preserve them all, he cites fourteen different human needs that must be taken into account in order to enrich and invigorate the human self. Instead, Mohammad Kamali and Jasser Auda begin with the genealogy of Maqaṣid. After explaining its textual origins, multiple classifications, and the history of its development, Kamali addresses Maqaṣid theory ‒ following its expansion beyond the traditional five objectives (the focus of Chapra’s book) and describes the main methodological challenges that have faced the field. Auda departs from Kamali by focusing on the relevance and promise of Maqaṣid for contemporary Islamic jurisprudence and thought ...